Anticipatory child fostering and household economic security in Malawi - Lauren Bachan (Demographic Research, 2014)
Background: While there is a rich literature on the practice of child fostering in sub-Saharan Africa, little is known about how fostering impacts receiving households, as few studies consider household conditions both before and after fostering. Despite the fact that circumstancessurrounding fostering vary, the literature's key distinction of fostering is often drawn along the simple line of whether or not a household is fostering a child. This paper argues that anticipation of fostering responsibilities, in particular, is a useful dimension to distinguish fostering experiences for receiving households. Objective: This paper examines the relationship between receiving a foster child and subsequent changes in household wealth. Particular emphasis is placed on how these changes are conditioned by differing levels of anticipation of the fostering event. Methods: This study uses data from Tsogolo la Thanzi (TLT), a longitudinal survey in Balaka, Malawi. Using data from 1754 TLT respondents, fixed effects pooled time-series models are estimated to assess whether and how receiving a foster child changes household wealth. Results: This paper demonstrates the heterogeneity of fostering experiences for receiving households.The results show that households that anticipate fostering responsibilities experience a greater increase in household wealth than both households that do not foster and those that are surprised by fostering. Conclusions: Households that anticipate fostering responsibilities exhibit the greatest increase in householdwealth. While fostering households that do not anticipate fostering responsibilities may not experience these gains, there is no evidence to indicate that such households are negatively impacted relative to households that do not foster. This finding suggests that additional childcare responsibilities may not be as detrimental to African households as some researchers have feared.